Colônia Rondinha/Santa Lúcia: colonização e religiosidade na região das Missões do Rio Grande do Sul (1921-1937). - Wesz, Mauro Marx (2016)
This research seeks to explain issues related to the settlement and historical representations undertaken by the community of Rondinha/Santa Lúcia/Caibaté, in the Missões of Rio Grande do Sul, southern region of Brazil, in the early years of the twentieth century. We take as axis of analysis the territorial appropriation of this location to a better understanding of the process of integration between individuals of different origins that occurred in the rural community of Rondinha/Santa Lúcia. Its settlement occurred from settlers and shifting cultivators, in this case, descendants of european immigrants who were seeking new properties for economic growing, and a group of other persons who were already living there, and were linked to agricultural activities and usually linked to ranchers historically present in that space. The foundation of the Santa Lucia village and the construction of the Sanctuary of Caaro present themselves as intrinsic aspects to understand the firsts activities while community of that society, and the notion of past benchmarks that should be followed. Also we propose to understand how this concept of missioneirism continues to be made among the Pilgrimage‟s of Caaró of penitential character, as well the production of their narratives, for this it‟s essential to relate every aspect mentioned above. That way we can explain a little more about the peculiarities of this place, and who were the agents involved in the tangle of existing social relations in this mixed colony in the early decades of the twentieth century.